ANALISA RASIO KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PADA KOPERASI ALBASIKO II KECAMATAN KINALI KABUPATEN PASAMAN BARAT - Mardahleni Mardahleni (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2017)
Cooperatives as a legal entity also need to look the development financial performance. Thus the cooperative can be found out how their abilities and how the efficiency should be carried out to maintain financial conditions to keep increasing over time. The purpose of this study was to know how the company's financial performance in the Cooperative Albasiko II during 2013-2015 using financial ratios. Cooperative performance Albasiko II in districts Kinali West Pasaman based on the liquidity ratio was not stable. Where the calculation of the ratio in 2013-2015 have increased and decreased. Based on the solvency ratio was not good than in 2013-2015 due to the cooperative debt increased every year. Pursuant to the profitability ratio was pretty good. From 2013 to 2014 increased quite high namely NPM by 22% to 31%. Although in 2015 dropped to 30%, which was not so significant. Keywords: Financial Performance, Liquidity, Solvency and Profitability